2003
DOI: 10.1007/s00417-003-0743-4
|View full text |Cite
|
Sign up to set email alerts
|

Phakomatous choristoma of the eyelid

Abstract: Phakomatous choristoma is an extraordinary rare tumor that probably develops from an abnormal separation or migration of cells from the lens placode into the mesodermal structures of the lid. Only 18 cases have been described so far, less than 5 in the European literature. This benign tumor may be confused with cutaneous adnexal neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…25 The natural history of phakomatous choristoma is not known. 6 In some of the previously reported cases, the mass had remained unchanged in size since birth, 9,11,12,14–16,18,22 whereas in several others gradual increase in the size of the lesion had been recorded. 1,2,46,8,10,17,23,24…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…25 The natural history of phakomatous choristoma is not known. 6 In some of the previously reported cases, the mass had remained unchanged in size since birth, 9,11,12,14–16,18,22 whereas in several others gradual increase in the size of the lesion had been recorded. 1,2,46,8,10,17,23,24…”
Section: Discussionmentioning
confidence: 90%
“…124 The site of the lesion has been either the eyelids or the anterior orbit. 124 However, there has been one instance of its occurrence in the corneal stroma. 25 The natural history of phakomatous choristoma is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One child was followed for 7.5 years and the other for approximately 16 months, without evidence of recurrence or residual tumor. [ 6 ] Because choristoma is classified as a benign tumor, many studies do not discuss recurrence. The case reported in this study showed benign tumor characteristics based on the preoperative MRI findings and the intraoperative observations.…”
Section: Discussionmentioning
confidence: 99%
“…Kurman et al [6] Seyed et al [7] GW P et al [8] A T-E et al [10] R S, et al [9] Chen et al [11] PF C, et al [1] M S, et al [17] M Z, et al [13] JC M-H, et al [12] G R [15] Y L et al [14] YW H, et al [17] Pan-CKs adjacent coverings of vessels and neural structures. [26] As no clear cleavage plane is found between the intraspinal lipoma and spinal cord, very few reports recommend complete surgical removal of an intraspinal lipoma as complete resection is associated with significant postoperative complications.…”
Section: Referencementioning
confidence: 99%